Peran Orang Tua Dalam Pembelajaran Jarak Jauh Menurut Paradigma Charlotte Mason - Olivia Wuwung; Berdinata Massang; Raven Neman; Refli Fransisko Bawiling (Pascasarjana IAKN Manado, 2021)
The purpose of this study is to know the role of parents in remote learning according to charlotte mason's paradigm at tateli's Christian junior high school, mandolang district and to know the challenges parents face in the long-distance learning process. It is a qualitative study using a descriptive approach. The subjects in this study are parents, students, and teachers. Data collection takes place through interviews, observations, documentaries. Researchers act as live interviews to collect data through parents, students and teachers. The results of the study indicate that the role of parents in distance learning according to the paradigm of Charlotte Mason in Christian Junior High School, Tateli, Kec. Mandolang, namely parents as teachers at home, as facilitators, motivators, influences, preparing a clean and healthy lifestyle, especially in character building. The obstacles faced by parents are that they have enough time to accompany their children to learn from home, lack of understanding of the material from parents. Difficulty in operating gadgets, not being able to provide facilities and infrastructure and looking at the educational background of parents who cannot yet teach their children well good. Efforts made by parents to overcome obstacles in distance learning are building good communication between parents, teachers, and students, learning to understand gadgets, practicing good habits for being honest, respecting each other, being responsible, disciplined, diligent in praying, worship, study God’s word, always be grateful and so on.